A review of load resource scheduling and control geared to the needs of power system scheduling - MENG Zhiquan; LOU Xiansi; SHI Han; XIE Yunyun; GUO Xiaorui; SUN Feifei (Zhejiang dianli, 2022)
In order to realize the energy transformation under the goal of carbon neutrality， new energy represented by wind power and photovoltaic power will serve as the main power supply for the future power system. However， the access of high-proportion renewable energy brings about high uncertainty and undermines system inertia， so much so that the scheduling resources of the traditional power system can no longer meet the scheduling demand of the future power system. Hence， a transformation from “the source changes with load” to “the interaction between source and load”. Therefore， this paper summarizes the load resource scheduling methods geared for power system scheduling. Firstly， from the perspective of power grid operation scheduling， the necessity of bringing controllable load into power grid operation scheduling is expounded， and controllable load is classified from five aspects： dispatching response time， dispatching response mode， users’ power consumption characteristics， energy transfer direction and load aggregator platform. Then， the influence of controllable load access on power system scheduling is analyzed from the aspects of modeling technology， scheduling form and scheduling architecture. Finally， combined with the current development of power system in China， the suggestion and prospect of controllable load resources participating in power grid operation scheduling are put forward.